Evaluation of Cell Lines for the Isolation of Foot-and-Mouth Disease Virus and Other Viruses Causing Vesicular Disease - Gray, Ashley R.; Wood, Britta A.; Henry, Elisabeth; Azhar, Mehreen; King, Donald P.; Mioulet, Valérie (Frontiers in Veterinary Science, 2020)
The most sensitive cell culture system for the isolation of foot-and-mouth disease virus (FMDV) is primary bovine thyroid (BTY) cells. However, BTY cells are seldom used because of the challenges associated with sourcing thyroids from FMDV-negative calves (particularly in FMD endemic countries), and the costs and time required to regularly prepare batches of cells. Two continuous cell lines, a foetal goat tongue cell line (ZZ-R 127) and a foetal porcine kidney cell line (LFBK-αVβ6), have been shown to be highly sensitive to FMDV. Here, we assessed the sensitivity of ZZ-R 127 and LFBK-αVβ6 cells relative to primary BTY cells by titrating a range of FMDV original samples and isolates. Both the ZZ-R 127 and LFBK-αVβ6 cells were susceptible to FMDV for >100 passages, and there were no significant differences in sensitivity relative to primary BTY cells. Notably, the LFBK-αVβ6 cell line was highly sensitive to the O/CATHAY porcine-adapted FMDV strain. These results support the use of ZZ-R 127 and LFBK-αVβ6 as sensitive alternatives to BTY cells for the isolation of FMDV, and highlight the use of LFBK-αVβ6 cells as an additional tool for the isolation of porcinophilic viruses.